Herding of Financial and Non-Financial Listed Companies: The Case of Indonesia - Gusni, Gusni; Dirgantari, Puspo Dewi; Pesakovic, Gordana (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 2 (2024)DO - 10.24843/JIAB.2024.v19.i02.p03, 2024)
The capital market is susceptible to herding behavior due to various global crises in recent decades, potentially leading to stress in the stock market, including in Indonesia. The purpose of this study is to identify herd behavior, including asymmetric conditions during market-up and down from the finance and non-finance industry listed in the Indonesia Equity Market. This study employs a cross-sectional dispersion approach to capture herding by employing daily closing stock price data from January 2015 to December 2022. The findings denote that herding behavior was not observed in the finance or non-finance sectors either before or during the COVID-19 pandemic. The asymmetric herding test results reveal that herding behavior is only identified in the non-finance sectors when the market is down. These results could aid capital market authorities in anticipating collective actions to uphold stability in the Indonesia non-finance listed companies, particularly during periods of heightened volatility amidst market downturns. Keywords: herding behavior, asymmetric herding, COVID-19 pandemic; finance and non-finance companies